2004
DOI: 10.1207/s15327914nc5001_12
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Induce Apoptosis in Human Leukemia U937 Cells Through Caspase- and Caspase-Calpain-Dependent Pathways

Abstract: Flavonoids are polyphenolic phytochemicals that are ubiquitous in plants and present in the common human diet. They may exert diverse beneficial effects, including antioxidant and anticarcinogenic activities. In this study we tested the apoptotic activity of 22 flavonoids and related compounds in leukemic U937 cells. Several flavones but none of the isoflavones or flavanones tested induced apoptotic cell death under these conditions, as determined by reduction in cell viability, flow cytometry, and oligonucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 26 publications
2
70
0
2
Order By: Relevance
“…For the cells treated with chrysin, cells stained with DAB (indicating apoptotic changes) were significantly increased compared to the controls. This is consistent with previous studies, which have reported an apoptosis-induction effect of chrysin in prostate cancer, lung cancer, leukemia and cutaneous melanoma cells (4,5,9,12).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…For the cells treated with chrysin, cells stained with DAB (indicating apoptotic changes) were significantly increased compared to the controls. This is consistent with previous studies, which have reported an apoptosis-induction effect of chrysin in prostate cancer, lung cancer, leukemia and cutaneous melanoma cells (4,5,9,12).…”
Section: Discussionsupporting
confidence: 94%
“…Flavonoids are a family of polyphenolic compounds synthesized by plants with a similar structure, which are categorized into anthocyanidins, flavanols, flavanones, flavonols, flavones and isoflavones according to their functional groups (4). Chrysin, a naturally active compound of the flavone group, shares a common flavone structure with additional hydroxyls at positions 5 and 7 of the A ring ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These flavonoids induced loss of mitochondrial transmembrane potential, elevation of reactive oxygen species production, release of mitochondrial cytochrome c into the cytosol, and subsequent induction of procaspase-9 with apigenin having the highest potency in inducing apoptotic effects. In another study, Monasterio et al (95) evaluated the potential of 22 flavonoids and related compounds by testing the apoptotic activity in leukemic U937 cells. In these studies, apigenin and several other flavones but not the isoflavones or flavanones tested were shown to induce apoptosis in U937 cells.…”
Section: Apigenin and Leukemiamentioning
confidence: 99%
“…Therefore, quercetin has received much attention as a promising anticancer drug with little toxicity when administered orally or intravenously [2,3]. The antitumor activity of quercetin has been tested in several cancers including breast [4], colon [5], gastric [6], leukemic [7] and bladder cells [8]. Anticancer actions were attributed to several cellular mechanisms including apoptosis by triggering the generation of ROS [9], and regulation of the cell cycle by modulating several molecular targets including p21 [10], cyclin B [11], p27 [12], and topoisomerase II [13,14].…”
Section: Introductionmentioning
confidence: 99%